Pengembangan Aplikasi Bimbingan dan Konseling “Circle” Berbasis Android sebagai Self Development untuk Korban Bullying - Akhmad Harum; Faturrahman Aulia; Muhammad Anas (Fakultas Dakwah dan Komunikasi, UIN Raden Fatah Palembang, 2023)
This research is an android-based Circle guidance and counseling service development research at SMK Negeri 10 Makassar that aims to produce an android-based guidance and counseling service application for students who are victims of bullying as well as guidance and counseling teachers at SMK Negeri 10 Makassar. This type of research is called R&D (research and development). This research was conducted through seven main stages: (1) initial research and information gathering (research and information collecting), (2) planning (planning), (3) preparation of the initial model format (developing a preliminary form of product), (4) conducting initial field trials (preliminary field testing), (5) conducting main product revisions, (6) conducting field trials of main models (main field testing), and (7) revising the operational model (operational product revision). The data collection techniques used in this study were questionnaires, observation, and interviews. Application product testing was then validated by 1 material expert and 1 media expert. This study used 3 guidance and counseling teachers as subjects and 6 students at SMK Negeri 10 Makassar. The method used to analyze the data is a quantitative descriptive analysis technique with a predetermined distribution of scores and scale categories. Based on the results of the research, shows that the developed android-based application is valid and practical to use for the provision of guidance and counseling services by guidance and counseling teachers to students who are victims of bullying at SMK Negeri 10 Makassar